SALT TOLERANCE OF BACTERIA ISOLATED FROM TROPICAL MARINE FISH AND PRAWN - SURENDRAN, P K; IYER, K MAHADEVA; GOPAKUMAR, K (Fishery Technology, 2017)
Salt tolerance of selected cultures of Pseudomonas, Moraxella, Vibrio, Micrococcus, Acinetobacter, and Flavobacteria/ Cytophaga were determined. More than 80% of the cultures belonging to each of the above genera, were capable of growth in presence of 1.5 to 3.5 la salt (NaCl) and at least 25 to 30% of the cultures in each group required 1.5 to 3.5 la salt for growth. F01 ty per cent each of Pseudomonas and Vibrio strains and 30% each of Moraxella, Micrococcus andFlavobacteria/Cytophaga strains tolerated 10% salt. Majority of the cultures belonging to the genet a Pseudomonas, Vibrio, Moraxella, JI;Jicrococcus, Acinetobacter and FlavobacteriajCytophaga were slightly halophilic (2 to 5% salt tolerant), about 25% especially of Micrococcus spp; moderately halophilicM (5 to 20% salt tolerant) and none 1rom Pseudomonas, Vibrio, Moraxella, Acinetobacter and Flavobacteria/Cytophaga spp. extremely halophilic (20 to 32% salt tolerant).